Participation in mass dog vaccination campaigns in Tanzania: Benefits of community engagement - Christian Tetteh Duamor; Christian Tetteh Duamor; Christian Tetteh Duamor; Felix Lankester; Felix Lankester; Emmanuel Mpolya; Elaine A. Ferguson; Paul CD. Johnson; Sally Wyke; Sarah Cleaveland; Katie Hampson; Katharina Kreppel; et al. (Frontiers Media S.A., 2022)
BackgroundCanine rabies causes about 59,000 human deaths each year globally but the disease can be eliminated by sustaining sufficient dog vaccination coverage over several consecutive years. A challenge to achieving high coverage is low participation of dog owners in vaccination campaigns. We explored whether and how previously identified contributory factors to low participation can be addressed through community engagement activities.MethodsWe engaged communities in two wards in Tanzania on dog behavior and handling, safe ways of interacting with dogs, and their perceptions of dog vaccination. We shared and elicited information from them through village meetings, video screenings, posters and leaflets and involved the leadership of one of the wards in planning and implementing a dog vaccination exercise to explore the feasibility of their participation. We assessed the impact of engagement activities with household surveys, meeting reports, observations and focus group discussions. We used a generalized linear mixed-effects model to identify predictors of knowledge and perceptions and compared knowledge amongst respondents before and after engagement activities. Qualitative data was analyzed inductively to explore perceptions of dog handling and vaccination and feasibility, opportunities and barriers to community leadership participation in organizing mass dog vaccination.Main findingsKnowledge of dog behavior, dog handling, and safe ways of interacting with dogs was positively associated with age (p < 0.0001), dog ownership (p = 0.0203), training (p = 0.0010) and previous experience of a dog bite (p = 0.0002); and was negatively associated with being afraid of dogs (p = 0.0061) and participation in a recent dog vaccination campaign (p = 0.0077). Knowledge was low before and significantly improved after engagement activities. The majority (92%) of respondents believed dog vaccination has no negative effects on dogs. Respondents perceived lack of bonding with their dog as a limitation to the ability to restrain a dog for vaccination. The community performed most roles assigned to them in the dog vaccination exercise, but barriers such as lack of motivation for volunteering exist.ConclusionEngaging communities regularly on dog vaccination can improve their knowledge of dog behavior and dog handling techniques, and may help improve owner participation in dog vaccination campaigns.